The Classification of Soils and Agriculture - I. Yu. Savin (Бюллетень Почвенного института им. В.В. Докучаева)
In the most of the cases, the practical use of knowledge about the soils is actualized by the use of the soil maps. The soil maps reflect the spatial inhomogeneities of soils in terms of accepted classification of soils. The prop on the basic classifications of soils leads to impossibility of the obtaining of the part of the properties of soils on the basis of traditional soil maps. However, these properties are important for the solving of agricultural tasks. The material composition, and also the processes occurring within the soils determine the plant growth, agrotechnics of their cultivation, and also terms, quantity, and quality of fertilizers, which are needed to be implemented for the soil. In other words, the classification of soils should be substantive and process for its use in agriculture. Taking into account actual state of the soil science, the special classification of soils may be replaced by geographic informational system, created for the purposes of agriculture. This system will contain the collected and linked together information about the spatial variation of separate important agronomic properties. It will also contain such data, which are necessary for geo-informational modeling of actual processes, occurring within the soil. Such computer system may serve as the basis for the assessment of soil quality for the purposes of one or another type of desirable land use, and also, for modeling of economic and ecologic efficiency of the land use. Only those properties which are necessarily should be taken into account in terms of the particular type of the use may be included into the assessment under each of the land use type.